Uji Stabilitas Spironolakton Terhadap Perubahan pH dengan Menggunakan Kromatografi Cair Kinerja Tinggi (KCKT) - Nelly Suryani; Yardi Supandi; Ririn Astri Sabdowati (Fakultas Farmasi Universitas Setia Budi, 2019)
Spironolactone is an aldosterone diuretic antagonist for hypertension. In practice spironolactone is sometimes combined with other drugs, and in unconscious patients the drug must use a feeding tube and be susceptible to instability. The object of this study was to see the effect of pH changes on spironolactone tablets which were crushed and suspended in water. The method of measuring spironolactone levels using High Performance Liquid Chromatography based on methods in the United State Pharmacopeia. Spironolactone suspension was made at pH 3, 5, 7, and 9 with sampling time in minutes 0, 15, 30, 45, and 60. The results showed that the level of spironolactone at pH 3 was ≤ 0%, pH 5 was 74% - 100%, at pH 7 it was in the range of 27% - 61%, and at pH 9 was 38% - 54%. This explains that percent of spironolactone at pH 3.7, and 9 at all sampling times did not match the minimum therapeutic level in the monograph. Only at pH 5 does the level of spironolactone still match the levels specified in the monograph. In this study it can be concluded that changes in pH can significantly reduce spironolactone levels in suspension.